Role of Herbs, Papain, and Microorganisms in Digestion - Saha, Dibyajyoti; Paul, Swati (Kathmandu University Journal of Science, Engineering and Technology, 2013)
The treatment of Ayurveda is totally based on natural herbs, and most importantly, each herb has certain medicinal value or property. Various herbs have various effects on our body. Herbs work by supplying different nutrients to the body. Some herbs work as a general tonic that cleanses, nourishes, and rebuilds on a cellular level. Enzymes are extremely active components in the digestion systems of all animals. Papain is used as an enzyme which helps in digestion, and it's usually produced as a crude, dried material by collecting the latex from the fruit of the papaya tree. The latex is collected after scoring the neck of the fruit. A purification step is necessary to remove contaminating substances. This purification consists of the solubilization and extraction of the active papain enzyme system through a government-registered process. This purified papain may be supplied as powder or as liquid. Microorganisms are also present in the digestive systems of all animals. Their main role is to break various components down in order to facilitate absorption. These findings highlight the importance of various herbs and papain enzyme, as well as different types of microorganisms, in digestion.